Comparative studies on the anti-neuroinflammatory and antioxidant activities of black and red goji berries - Vanessa Magalhães; Ana Rita Silva; Bruna Silva; Xiaoying Zhang; Alberto C.P. Dias (Journal of Functional Foods, 2022)
Goji berries have several bioactivities and are consumed as food or used in folk medicine. In this study, the methanolic extracts from red and black goji berries were compared regarding their anti-inflammatory and antioxidant activities. Black goji berries extract has revealed significantly higher anti-inflammatory activity, in either biochemical assays or via decreasing the release of nitric oxide and inhibiting the gene expression of pro-inflammatory cytokines in LPS-stimulated BV2 microglial cells, in comparison with the red goji berries extract. Black goji berries’ extract has also revealed a significantly higher antioxidant activity, in comparison with the red goji one. Inflammation and related oxidative stress have been brought to light as underlying mechanisms in several chronic diseases, e.g. neurodegenerative diseases. Our results show that these goji berries, particularly the black ones, can have the potential to be a source of pharmacologically active compounds in diseases with an inflammatory and oxidative background.